Process model and awareness in SCM. - Estublier, Jacky
The development of large and complex systems, under hard time constraints, requires the participation of many developers working concurrently. SCM systems allow concurrent access to software artifacts, but provide poor support to maintain data consistency when concurrent changes are performed on the same artifacts. This problem can be reduced if developers are aware of the others work and warned about the conflicts that may arise, allowing the users to manage the risks more effectively.Awareness, without any knowledge about the cooperative process and system models cannot help much, and indeed is not very much used today. We claim that awareness takes its potential only when it takes into account the cooperative process, and the system model in use. This paper, based on the experience gained with our tool Celine, explores the relationships between awareness, process and system models, and shows how the knowledge of these models can be used to improve the relevance of an awareness system.